The Rac GTP Exchange Factor TIAM-1 Acts with CDC-42 and the Guidance Receptor UNC-40/DCC in Neuronal Protrusion and Axon Guidance - Demarco, Rafael S. (Public Library of Science, 2012)
The mechanisms linking guidance receptors to cytoskeletal dynamics in the growth cone during axon extension remain mysterious. The Rho-family GTPases Rac and CDC-42 are key regulators of growth cone lamellipodia and filopodia formation, yet little is understood about how these molecules interact in growth cone outgrowth or how the activities of these molecules are regulated in distinct contexts. UNC-73/Trio is a well-characterized Rac GTP exchange factor in Caenorhabditis elegans axon pathfinding, yet UNC-73 does not control CED-10/Rac downstream of UNC-6/Netrin in attractive axon guidance. Here we show that C. elegans TIAM-1 is a Rac-specific GEF that links CDC-42 and Rac signaling in lamellipodia and filopodia formation downstream of UNC-40/DCC. We also show that TIAM-1 acts with UNC-40/DCC in axon guidance. Our results indicate that a CDC-42/TIAM-1/Rac GTPase signaling pathway drives lamellipodia and filopodia formation downstream of the UNC-40/DCC guidance receptor, a novel set of interactions between these molecules. Furthermore, we show that TIAM-1 acts with UNC-40/DCC in axon guidance, suggesting that TIAM-1 might regulate growth cone protrusion via Rac GTPases in response to UNC-40/DCC. Our results also suggest that Rac GTPase activity is controlled by different GEFs in distinct axon guidance contexts, explaining how Rac GTPases can specifically control multiple cellular functions.